Determination of blood glucose using an oxidase-peroxidase system with a non-carcinogenic chromogen. Issue 2 (March 1969) - Trinder, P.
Abstract : Manual and automated methods for the determination of blood glucose have been devised using an oxidase/peroxidase system, with dl adrenaline, a non-carcinogen, as oxygen acceptor. The manual technique employs a stable single solution protein precipitant and the other reagents used are also stable. The automated methods are operated at 40/hr sample speed and washover between samples, over a very wide concentration range, is negligible.